Kepemimpinan Umar bin Khattab dan Institusionalisasi Peradaban Islam Awal - mukhamad usamah (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2026)
The leadership of Umar ibn Khattab played a pivotal role in the institutional development of early Islamic civilization following the death of Prophet Muhammad. As the second caliph, Umar introduced systematic reforms that shaped the administrative, legal, and financial foundations of the Islamic state. His leadership was characterized by strong governance, social justice, and the establishment of various institutions such as the diwan (state registry), judiciary systems, regional administration, and public treasury (baitul mal). This study employs a qualitative approach using historical analysis and literature review as its primary methods. The findings reveal that Umar’s governance significantly contributed to the institutionalization of Islamic civilization, providing a structural model that influenced subsequent Islamic governance for centuries. These insights offer important contributions to the study of Islamic political history and the evolution of Islamic leadership. Abstrak Kepemimpinan Umar bin Khattab memainkan peran penting dalam pengembangan institusional peradaban Islam pada masa awal, pasca wafatnya Nabi Muhammad SAW. Sebagai khalifah kedua, Umar memperkenalkan berbagai reformasi sistematis yang membentuk fondasi administratif, hukum, dan keuangan negara Islam. Kepemimpinannya ditandai dengan tata kelola yang kuat, keadilan sosial, serta pendirian berbagai institusi seperti diwan (catatan negara), sistem peradilan, administrasi wilayah, dan baitul mal (perbendaharaan negara). Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis sejarah dan studi kepustakaan. Hasil kajian menunjukkan bahwa pemerintahan Umar secara signifikan berkontribusi terhadap institusionalisasi peradaban Islam dan menjadi model struktural yang memengaruhi sistem pemerintahan Islam pada masa-masa berikutnya. Temuan ini memberikan kontribusi penting bagi studi sejarah politik Islam dan perkembangan kepemimpinan Islam.